Performance measurement scale for facilities management service in Lagos-Nigeria. Issue 2 (15th May 2017) - Koleoso, Hikmot Adunola; Omirin, Modupe Moronke; Adewunmi, Yewande Adetoro
Abstract : Purpose: Literature established that applicable parameters must be used in determining facilities management (FM) performance in any market; otherwise, findings could be confusing and misleading. This is particularly relevant to Nigeria where FM application is in its infancy and seriously constrained by particular socio-economic conditions which make it prone to crises situations such as frequent power outages and surges, abundance of fake and adulterated construction materials and equipment, heavy presence of unqualified artisans, poor transparency and terribly chaotic and unpredictable traffic to mention a few. Hence, this research aims to identify contextual parameters for evaluating performance of FM service in office buildings in Lagos, reflecting these peculiarities. Design/methodology/approach: The research adopts survey design, using self-administered questionnaires that were served on building occupants. Means and standard deviation were used in the analyses. Factor analysis was used in identifying the important factors or constructs and to confirm the practical significance of the measures. Findings: The study developed a multi-item scale of 41 measures for evaluating performance of facilities managers in offices in Lagos, Nigeria. The scale comprises three major dimensions, i.e. "financial", "quality of service" and "crises response and management". Using factor analysis, the study identified five important factors, two of which (comprising ten new measures) have not been featured in previous studies. Practical implications: The developed performance measurement scales (PMS) can be applied to FM performance evaluation, management and control in the Nigerian context. The PMS and identified factors would also aid FM policy formulation, resource allocation and facilities review. Originality/value: The research is considered the first to develop a PMS for FM in office facilities in Lagos, Nigeria. The new factors and measures that were uncovered in the study makes it possible to evaluate the Nigerian facility manager's ability to manage the near-crises challenges imposed by the peculiar socio-economic context. Furthermore, the scale adopts simplistic financial success criteria, which makes it relevant and easy to use for the poor financial record disclosing and research-averse Nigerian audience. It is also more relevant to the less strategic and more operational task-based Nigerian FM context and by extension, to the context of other developing countries with similar socio-economic features.